ZIELONA KSIĘGA. OPTYMALNA WIZJA KODEKSU CYWILNEGO RZECZYPOSPOLITEJ POLSKIEJ - Radwański, Zbigniew (Wydział Prawa i Administracji UAM, 2007)
The civil code currently binding in Poland was adopted in 1964, but it has been recently substantially amended. Those amendments have been passed to repeal the institutions that were typical of the former socialist system, and to create new institutions of a democratic state character, addressing the needs o f a market economy. Those amendments, however, have somewhat impaired the cohesion o f the entirety o f the code. Moreover, many new institutions, especially those regulated by EU directives, have been left out, that has led to a substantial disintegration o f the civil law system, and weakened the function o f the code that is to hold the legal provisions together. With the above in mind, the Civil Law Codifying Commission, composed of 12 independent civil law theorists and judges of the Supreme Court, has initiated a discussion on the necessity o f a new civil code that would be based on the values included in Poland’s Constitution of 1997, and which would also incorporate Community law, and provide for the principles of modern economic activity. The Green Book contains a vision o f such codification and includes, in its annex, material complementing certain specific issues. The Book is to provide grounds for a further discussion on the contents of the new code. The draft provisions and suggestions presented in the Book indicate the practicality of drafting a new civil code followed by a new code of civil procedure.
GREEN BOOK. THE OPTIMAL VERSION OF THE CIVIL CODE OF THE REPUBLIC OF POLAND